Characteristics of preblended pork during cooler storage - Kastner, Curtis L.; Choi, Y.I.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five pork carcasses were used to determine the effects of hot boning and various combinations of salt (0, 1.5, or 3.0%) and a phosphate mixture (0 or 0.5%) on bacteria, TBA (measure of fat rancidity), and pH values of preblended pork (preblends). In both HB (hot boned within 2 hr postmortem) and CB (conventionally boned at 24 hr postmortem) preblends, salt increased (P<.05) TBA values (indicates increased rancidity) and decreased (P<.05) growth of psychrotrophic bacteria, whereas phosphate increased (P<.05) pH and decreased TBA values. Salt levels could be reduced from 3.0 to 1.5% in preblends without storage problems, if phosphate (0.5%) was included. Phosphate (mixture pH 7.2) had little influence on microbial growth of preblends during cooler storage.
Keywords: Swine; Preblended pork; Cooler storage